COACHING LEADER coaching skills for leading through complexity. - Day, Ian (Business consultant) (ROUTLEDGE, 2026)
The Coaching Leader: Coaching Skills for Leading through Complexity sets out a new approach to leadership by synthesizing coaching skills, leadership theory, and practice.This approach enables the Coaching Leader to make a crucial difference to individuals and organizations in the current socio-economic climate. This book details the 'why,' 'what,' and 'how' of being a Coaching Leader and presents a business case for leadership which constantly evolves to match the needs of the context. This book explores alternative leadership theories including adaptive leadership, servant leadership, and the humble leader. Readers are given the tools to develop the mindset and skills to support practical approaches to leadership theories in the workplace and develop a reflective self-awareness.This book is ideal for those studying leadership or coaching at a postgraduate level, MBA students, or organizational leaders looking to improve their leadership skills for greater impact.
Keywords: Executive coaching.; Leadership.; elektronické knihy; electronic books